Neuroethics and Religion: some Jewish thoughts. A response to Alberto Carrara - Garasic, Mirko Daniel (Studia Bioethica, 2017)
In the course of his interesting paper, Alberto Carrara raises a number of important points. Though unable to provide a deeper analysis in this occasion, in this brief response, I will focus on some of those points. Hopefully, the insights provided will be sufficient to expand the discussion on Neuroethics and Religion -in the specific building a number of bridges between Catholicism and Judaism vis-à-vis Transhumanism and Posthumanism. Out of intellectual honesty, I should state upfront that I will do so with the awareness of having to rely more on my expertise in bioethics than of Judaism.